EVALUATION OF COTTON GENOTYPES FOR DROUGHT TOLERANCE USING PEG-6000 WATER STRESS BY SLANTING GLASS PLATE TECHNIQUE - A. G. BABU,; B. C. PATIL,; K. N. PAWAR, (The Bioscan, 2014)
Twelve Gossypium hirsutum genotypes viz., CPD-750, Sahana, ARB-9701, CNH-120MB, GIHV-218, BS-279, RAH-101, GJHV-477, F-2228, KH-155, L-761 and LH-2076 were evaluated for drought tolerance using PEG6000 water stress at germination stage. The genotypes were subjected to different osmotic potentials (0.0 MPa, 0.05 MPa, -0.148 MPa, -0.295 MPa, -0.491 MPa, -0.735 MPa and -0.846 MPa) by slanting glass plate technique. The genotypes were evaluated for percent seed germination and seedling vigour traits at 12th and 18th day showed maximum concentration of PEG-6000 for the germination is 25% (-0.735 MPa) and at this concentration the shoot growth was completely inhibited in all the genotypes. As the PEG concentration increases there was an increase in root to shoot ratio. In conclusion the genotypes which found tolerant to the increased osmotic potential were BS-279, CNH-120MB, GIHV-218 and ARB-9701 whereas, L-761, KH-155 and LH-2076 were found as drought sensitive genotypes.